Prognostication of Traumatic Brain Injury using International Mission for Prognosis and Analysis of Clinical Trials in Traumatic Brain Injury score in Nepalese Cohort - Jha, Binit Kumar; Jha, Prabhat; Khambu, Bikesh; Shrestha, Rajendra; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2021)
Introduction: Traumatic brain injury disease of major importance globally. Prognostic models are useful for making decisions in the clinical practice. The aim of this study was to assess the accuracy of International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT) score in predicting outcome in moderate to severe TBI at 3 months. Materials and Methods: All patients admitted to National Trauma Center, National Academy of Medical Sciences with moderate to severe traumatic brain injury from February 2020 to February 2021 were included in the study. IMPACT scores (core/extended core/ lab) were recorded separately at admission. Outcome was measured with Glasgow Outcome Scale (GOS) at the time of discharge and at six months. Correlation between observed and predicted outcomes was evaluated by Pearson’s correlation coefficient (r). Sensitivity and specificity were plotted in the receiver-operating characteristic (ROC) curve, and the area under the curve (AUC) was calculated to determine the discrimination ability of this prognostic model.Results: A total of 112 patients were enrolled in the study. Eighty (71.4 %) patients had moderate and 32 (28.57 %) had severe TBI. The median age was 33 years with male preponderance (M: F=4:1). Thirty three (29.5 %) patients died within 6 months of TBI, and 38 (33.9 %) patients  had an unfavorable outcome. Pearson correlation coefficient showed good correlation between observed and predicted outcomes. Hosmer-Lemeshow test showed good model fit for IMPACT core, IMPACT extended and IMPACT lab in diagnosing mortality and unfavorable outcome in six months (p>0.05). The ROC curve indicated that all 3 models could accurately discriminate between favorable and unfavorable outcomes, as well as between survival and mortality (unfavorable outcome AUC= 0.905, 0.940, 0.955; mortality AUC= 0.875, 0.914, 0.917 respectively) in our patient population.Conclusion: The IMPACT score is a good prognostic model to predict 6-month outcomes in moderate to severe TBI at admission in Nepalese patient population. Among the three IMPACT models, IMPACT lab has the greatest discriminating ability.